1023 The Role of Social Media in Disseminating Plastic Surgery Research: The Relationship Between Citations, Altmetrics and Article Characteristics. (4th May 2021) - Grant, M; Scott-Bridge, K; Wade, R
Abstract: Background: Social media (SoMe) enable the dissemination of content immediately and directly to interested end-users. Alternative metrics (altmetrics) are non-traditional bibliometrics which describe the exposure and impact of an article on freely available platforms such as Twitter and Facebook. Altmetrics within days of publication are associated with ultimate citation counts in various medical disciplines, except plastic surgery which represents the rationale for this study. Method: Altmetric explorer was used to extract altmetrics and citation rates for articles published during 2018 in Plastic and Reconstructive Surgery (PRS), the Journal of Plastic, Reconstructive and Aesthetic Surgery, the Annals of Plastics Surgery and Plastic Surgery. Multivariable negative binomial regression was used to estimate the relationship between citations and predictors (presented as the incidence rate ratio, IRR with 95% confidence interval, CI). Results: Overall, 1215 articles were captured. On average, articles published in PRS were cited nearly five times as often as articles published elsewhere (adjusted IRR 4.77 [95% CI 2.36, 9.62]). Overall, SoMe mentions were positively associated with citation rates (adjusted IRR 1.01 [95% CI 1.01, 1.1]); marginal analysis showed that 45 mentions translated to one extra citation. Conclusions: Dissemination of plastic surgery research through SoMe channels are associated with significant improvements in short term citations rates.